Assessing Attitudes of Medical Students towards First Contact with Patient in Tehran (2016-17) - Azargashb, Eznollah; Heidarnia, Mohamad Ali; Derisi, Mohamad Mehdi; Zamani, Amir; Keyvanfar, Amirreza; Mohammadi, Mohammad; Sadeghzadeh, Nima; Mousavifar, Mirsaid (Novelty in Biomedicine, 2018)
Background: Early experience of clinical arena as first situations can be effective in selection or refusing medicine as profession is so important that programmers and administrators should consider these settings as one of the most elements in educational programs. Materials and Methods: This study was a cross-sectional study and including presently studying students in medicine field of medical sciences universities. Sample size was estimated for 275 students. Participants were selected from schools of medicine: Iran University (IUMS), Shahid Beheshti University, and Islamic Azad University using stratified random sampling method. Data was collected in March of 2016 by a researcher made questionnaire determined its validity and reliability. Data was analyzed using chi-squared test, t-test, Mann-Whitney and Kruskal-Wallis test. Results: Mean score of medical students’ attitude from 15 five-degree scale questions was 51.22 ± 6.32. The mean scores of attitude in men and women were 51.37±6.16 and 51.06±6.53, respectively (p=0.687). Overall, 13.8 % of students had positive attitude towards first contact with patient, 10.5 % of students had negative attitude and 75.6 % had no opinion. The mean scores of attitude towards first contact with patient in Iran university, Shahid Beheshti university and Islamic Azad university were 50.40±5.00, 52.71±5.91 and 46.12±5.97, respectively (p<0.001). The mean scores of attitude towards first contact with patient in reformed educational system and old educational system were 52.35±5.83 and 46.12±5.97 respectively, with a significant difference between two types of educational system (p<0.001). Conclusion: As respects more positive attitude of students in reformed educational system in comparison with old educational system, special attention to courses of early contact with patient may contribute to decreasing educational insufficiency and distance between theory and practice and lead to the satisfaction all of beneficiaries.